The synthetic composite materials using PHBV, nZVI and biochar enhanced denitrification performance in water treatment. Issue 6 (December 2022) - Zhu, Yuen; Li, Lingzhi; Liu, Hailong; Zhang, Guixiang; Zheng, Jingyi; Feng, Kai; Wang, Haipeng; Li, Hua
Abstract: Solid carbon source (SCS)-based denitrification is a promising technique for nitrogen removal from sewage. However, a sustainable and effective supply of carbon sources, crucial to denitrification performance, has always been challenging. This study developed four synthetic SCSs: biochar (BC), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), PHBV loaded on biochar (BCP), and PHBV loaded on biochar-supported nanoscale zero-valent iron (BCPF), to examine their denitrification efficiency enhancement. Insufficient carbon sources caused low nitrate removal (<45%) in the BC reactor during the entire experiment. At the biofilm formation stage (influent nitrate: 40 mg L -1 ), the relatively higher nitrate removal in biochar-based SCS reactors than in the P reactor in the first 4 h indicated that the biochar's rapid release of carbon sources played a priming role in denitrification. Then, the subsequent sharp decrease in nitrate removal revealed the biochar's unsustainable release of carbon sources for the denitrifiers. Similar to the P reactor, the nitrate removal in BCP and BCPF reactors gradually increased after 12 h until the 48 h mark, where the high nitrate removal efficiency was stabilized (P: 79.93%−93.74%, BCP: 86.90%−100%, and BCPF: 91.68%−100%), except in the BC reactor. Evidently, the decomposed products from PHBV provided sustainable carbon sources for the denitrifiers. Compared with the P reactor in the continuous running stage, BCP and (especially) BCPF reactors exhibited excellent resistance to load impact. Here, PHBV supplied sustainable carbon sources and electron donors for denitrification, while nZVI served as extra electron donors. The biochar dominantly provided habitats for denitrifiers and functioned as an electron mediator. Graphical Abstract: ga1 Highlights: A novel SCSs was synthesized by loading PHBV on biochar-supported nZVI. BCPF had the excellent denitrification performance and resistance to load impact. Biochar provided habitats for denitrifiers and served as electron mediator. PHBV provided the sustainable carbon sources and electron donors for denitrifiers.